2023
DOI: 10.3390/fire6110421
|View full text |Cite
|
Sign up to set email alerts
|

Bushfire Management Strategies: Current Practice, Technological Advancement and Challenges

Sahan Bandara,
Satheeskumar Navaratnam,
Pathmanathan Rajeev

Abstract: Bushfires are classified as catastrophic disasters capable of inflicting significant destruction. The key detrimental consequences of bushfires include the loss of human lives, trauma within communities, economic losses and environmental damage. For example, the estimated economic loss from the September 2019 to March 2020 bushfires in New South Wales (Australia) was about AUD 110 billion, including more than 3000 burned houses. There has been a notable increase in both the frequency and intensity of bushfires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 138 publications
(201 reference statements)
0
0
0
Order By: Relevance
“…Moreover, it was also found that approximately 80% of non-fire alarms could be reduced in the actual fire alarms that occurred at Institute K during the 5-year period examined. Bandara et.al [3] proposed the changed circumstances of landscapes, vegetation patterns, weather conditions and ecosystems account for the complexity. Therefore, continual attention was essential for the development of bushfire management strategies.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, it was also found that approximately 80% of non-fire alarms could be reduced in the actual fire alarms that occurred at Institute K during the 5-year period examined. Bandara et.al [3] proposed the changed circumstances of landscapes, vegetation patterns, weather conditions and ecosystems account for the complexity. Therefore, continual attention was essential for the development of bushfire management strategies.…”
Section: Related Workmentioning
confidence: 99%